Para a biografía de Aníbal Otero como lingüista: documentos e datos inéditos ou descoñecidos - Alonso Montero, Xesús (Madrygal. Revista de Estudios Gallegos, 2009)
The author aims to approach the admired linguist Aníbal Otero (1911-1974) by reviewing the most important aspects of his career as a researcher in Galician linguistics through some unpublished personal documents, paying special attention to his collaboration in ALPI and his arrival to the Galician Academy.
Keywords: Galician linguistics; ALPI; Galician Academy